Digital Delivery of Meditative Movement Training Improved Health of Cigarette-Smoke-Exposed Subjects - Payne, Peter; Fiering, Steven; Zava, David; Gould, Thomas J.; Brown, Anthony; Hage, Paul; Gaudet, Carole; Crane-Godreau, Mardi (Frontiers in Public Health, 2018)
Many FA who flew prior to the ban on smoking in commercial aircraft exhibit an unusual pattern of long-term pulmonary dysfunction. This randomized controlled study tested the hypothesis that digitally delivered meditative movement (MM) training improves chronic obstructive pulmonary disease (COPD)-related symptoms in flight attendants (FA) who were exposed to second-hand cigarette smoke (SHCS) while flying. Phase I of this two-phase clinical trial was a single-arm non-randomized pilot study that developed and tested methods for MM intervention; we now report on Phase II, a randomized controlled trial comparing MM to a control group of similar FA receiving health education (HE) videos. . Primary outcomes were the six-minute walk test and blood levels of high sensitivity C-reactive protein (hs-CRP). Pulmonary, cardiovascular, autonomic and affective measures were also taken. There were significant improvements in the six-minute walk test, the Multidimensional Assessment of Interoceptive Awareness (MAIA) score, and the COPD Assessment Test. Non-significant trends were observed for increased dehydroepiandrosterone sulfate (DHEAS) levels, decreased anxiety scores and reduced blood hs-CRP levels, and increased peak expiratory flow (PEF). In a Survey Monkey questionnaire, 81% of participants who completed pre and post testing expressed mild to strong positive opinions of the study contents, delivery, or impact, while 16% expressed mild negative opinions. Over the course of the year including the study, participant adoption of the MM practices showed a significant and moderately large correlation with overall health improvement; Pearson's R=0.62, p<0.005. These results support the hypothesized benefits of video-based MM training for this population. No adverse effects were reported. This trial is registered at ClinicalTrials.gov https://clinicaltrials.gov/ct2/show/NCT02612389/.